6xy-17=4xy+11

Simple and best practice solution for 6xy-17=4xy+11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6xy-17=4xy+11 equation:


Simplifying
6xy + -17 = 4xy + 11

Reorder the terms:
-17 + 6xy = 4xy + 11

Reorder the terms:
-17 + 6xy = 11 + 4xy

Solving
-17 + 6xy = 11 + 4xy

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4xy' to each side of the equation.
-17 + 6xy + -4xy = 11 + 4xy + -4xy

Combine like terms: 6xy + -4xy = 2xy
-17 + 2xy = 11 + 4xy + -4xy

Combine like terms: 4xy + -4xy = 0
-17 + 2xy = 11 + 0
-17 + 2xy = 11

Add '17' to each side of the equation.
-17 + 17 + 2xy = 11 + 17

Combine like terms: -17 + 17 = 0
0 + 2xy = 11 + 17
2xy = 11 + 17

Combine like terms: 11 + 17 = 28
2xy = 28

Divide each side by '2y'.
x = 14y-1

Simplifying
x = 14y-1

See similar equations:

| -16=-259+x | | 64x^2-144x+585=0 | | x/4-3=33 | | 9y=5-(y+6) | | -6(7x-8)=12 | | c+160=1850 | | n+7=8n | | -100=-7x-5(8+x) | | -0.7+1.15=-0.4x+1.75 | | 4y^2=12 | | (4m+5)2= | | 1.83/9 | | -31=x-54 | | 5x-7=2(3x-5) | | 4(t-3)+5t=t-3 | | 12x^2+33x-9=y | | 1.4x-4.8=0.6x-3.28 | | 750000+5+800000+3=1x | | 1.5x+2.7=0.8+0.95 | | 88-w=173 | | 3/(2x-3)=2/(x+5) | | 4x+1/7x=6 | | 750000+5x=800000+3x | | 4x-8+3x=12+6x | | y-26=-28 | | -6+3(-1-b)=19 | | (3x+6)+(3x)+(3x+5)=(3x)+(3x)+(4x+6) | | -3x+7=2y+9 | | 5+3(x-2)=-1 | | 2/3(3x+5)=-24 | | 4/9=-y/3 | | 9x+1=10x+12 |

Equations solver categories